Comparison between Caribbean and eastern Pacific coral reefs - Cortés, Jorge (Revista de Biología Tropical, 1993)
The temporal and spatial distance separating the Caribbean and the eastern Pacific is short, as little as 50 km (Leschine 1981) and around 3.5 million years (Coat.es et al. 1992). This separation has resulted in very different oceanographic settings and coral reefs on both sides of the Central American isthmus (Glynn 1982). In this paper I extend Glynn's comparisons to include historical development of the reefs and more recent contrasting data from both sides.